Pegaruh Self Efficacy, Stres Kerja, dan Motivasi Kerja Terhadap Perilaku Kerja (Studi Pada Driver Gojek di Yogyakarta) - Maida Ubang; Didik Subiyanto Subiyanto; Tri Ratna Purnamarini Purnamarini (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to determine the effect of self efficacy, work stress, and work motivation on work behavior, with a case study of Gojek drivers in Yogyakarta. The research employs a quantitative approach, with data collected through questionnaires. The sampling technique used is non-probability sampling with an accidental sampling approach, in which samples were selected based on Gojek drivers who happened to be encountered and agreed to become respondents. The total number of respondents in this study is 105 active Gojek drivers operating in the Yogyakarta area. Data analysis was conducted using multiple linear regression to examine the extent to which the independent variables self efficacy, work stress, and work motivation affect the dependent variable, namely work behavior. The results of the study show that self efficacy, work stress, and work motivation have a significant influence, both simultaneously and partially, on the work behavior of Gojek drivers. These findings indicate that increasing self efficacy, proper management of work stress, and strong work motivation can promote more productive and professional work behavior.